Assessment of the Frequency of Online Searches for Symptoms Before Diagnosis: Analysis of Archival Data - Hochberg, Irit; Allon, Raviv; Yom-Tov, Elad (Journal of Medical Internet Research, 2020)
Surveys suggest that a large proportion of people use the internet to search for information on medical symptoms they experience and that around one-third of the people in the United States self-diagnose using online information. However, surveys are known to be biased, and the true rates at which people search for information on their medical symptoms before receiving a formal medical diagnosis are unknown.